Characterization of public space forms in traditional Chinese villages based on spatial syntax: Zhangli village as an example - Yang Zhao; Zihui Luo; Kai Huang (Journal of Asian Architecture and Building Engineering, 2025)
Traditional villages serve as witnesses to history and culture and as the centers of production and life. Studying their spatial characteristics and influencing factors can provide profound insights into their formation, development, and inheritance. Taking CAI’s ancient residential buildings in Zhangli Village, Quanzhou as a case study, this paper utilizes space syntax and abstract topological relations to quantitatively analyze three morphological characteristics of public space: (1) “Ancestral halls” and “Academies” are situated at the core of visual space, representing significant spatial elements within the village, with high visual appeal and status; (2) The spatial layout of “roadways” and “gates” caters to the needs of internal settlements, with their accessibility significantly varying in different directions. However, the high topological depth restricts exploration within the internal space; (3) The village provides residents with spaces for various types of public activities. Furthermore, this paper qualitatively explores the factors influencing the spatial form of Cai’s ancient dwellings from the perspectives of nature, economy, and culture, including topography, hierarchical order, geomancy principles, ethnic economic development, production, and lifestyle. Accordingly, the paper proposes corresponding protection and development strategies, offering a reference for the sustainable development of traditional villages in the future.